Protracted vomiting as the presenting sign of posterior fossa mass lesions. Issue 11 (November 1987) - Torrealba, G; Del Villar, S; Arriagada, P
Abstract : Four patients with mass lesions of the posterior fossa experienced protracted vomiting as their only symptom for extended periods of time. The responsible lesions were a cerebellar tumour in two patients, a ventricular cysticercus in one patient, and a giant vertebral artery aneurysm in another. All four cases had compression or displacement of the floor of the fourth ventricle, where the "vomiting centre" has been located. The value of vomiting as a sign of a posterior fossa lesion is emphasised.